2014
DOI: 10.1002/aqc.2446
|View full text |Cite
|
Sign up to set email alerts
|

Assessing sperm whale (Physeter macrocephalus) movements within the western Mediterranean Sea through photo‐identification

Abstract: ABSTRACT1. The Mediterranean sperm whale sub-population is considered 'Endangered' by both ACCOBAMS and the IUCN. Conservation policies require protected species populations to be monitored, but the distribution and movements of sperm whales across the Mediterranean Sea are still poorly understood.2. To provide insight into sperm whale movements, the photo-identification catalogue from the Strait of Gibraltar was compared with seven other collections: (a) the North Atlantic and Mediterranean Sperm Whale Catalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…Higher relative abundance was found at 800 m depth in the waters surrounding Ventotene island, between Ponza and Ventotene, and in a northern zone bordering the highly suitable area for fin whales. This seems consistent with previous studies reporting that sperm whales select for two main habitats: one where complex topographical features (escarpments, canyons, seamounts) characterize the sea floor and one where downwelling or upwelling water movements are associated with frontal zones in higher seas (Aïssi, Fiori, & Alessi, 2012;Arcangeli et al, 2017;Carpinelli et al, 2014;Fiori, Giancardo, Aïssi, Alessi, & Vassallo, 2014;Gannier & Praca, 2007;Mussi, Miragliuolo, Zucchini, & Pace, 2014;Pace, 2016;Pace et al, 2018). In this way, sperm whales would be able to capitalize on the food resources (cephalopods) available in both areas by shifting between different prey targets (Gannier et al, 2002).…”
Section: Sperm Whalessupporting
confidence: 92%
“…Higher relative abundance was found at 800 m depth in the waters surrounding Ventotene island, between Ponza and Ventotene, and in a northern zone bordering the highly suitable area for fin whales. This seems consistent with previous studies reporting that sperm whales select for two main habitats: one where complex topographical features (escarpments, canyons, seamounts) characterize the sea floor and one where downwelling or upwelling water movements are associated with frontal zones in higher seas (Aïssi, Fiori, & Alessi, 2012;Arcangeli et al, 2017;Carpinelli et al, 2014;Fiori, Giancardo, Aïssi, Alessi, & Vassallo, 2014;Gannier & Praca, 2007;Mussi, Miragliuolo, Zucchini, & Pace, 2014;Pace, 2016;Pace et al, 2018). In this way, sperm whales would be able to capitalize on the food resources (cephalopods) available in both areas by shifting between different prey targets (Gannier et al, 2002).…”
Section: Sperm Whalessupporting
confidence: 92%
“…In particular, three individuals (all immature males), showed transfers from north to south and vice versa, being recorded in both seas 1–2 months apart during a summer. This is analogous to other findings (Frantzis et al ., ; Carpinelli et al ., ), involving only males, thus suggesting that Mediterranean sperm whales behave in a similar way to those in other places, where males move between feeding and breeding grounds whereas females with their calves are more sedentary. Comparison between photo‐identification databases is still quite rare in the Mediterranean Sea, but the few recent attempts (Carpinelli et al ., ; Rendell et al ., ) have demonstrated that it could help to reveal new important information about sperm whale movements.…”
Section: Discussionmentioning
confidence: 82%
“…The analysis of continuous movement showed diffusion rates (a quantification of the rate a population spreads spatially) dropping to zero over time scales >1 year (Figure (a)) and displacements stabilizing at 400–600 km over similar time‐scales (Figure (b)), indicating home range sizes in the order of 1000 km across, very similar to estimates derived for sperm whales in the Pacific. Noting that maximum straight‐line distance between any pair of identification locations reported here is 970 km, these results suggest that individuals use the entire western basin (see also Carpinelli et al ., ). The lagged identification rate analysis across areas supported this qualitative assessment in that there were non‐zero probabilities of re‐identification in different areas over time lags ranging up to >9 years (Figure ), but also indicated that the probability of an individual being re‐sighted in an area different from its first sighting was lower than the probability of being re‐sighted in the same area, suggesting some restriction of movement between the two areas.…”
Section: Resultsmentioning
confidence: 97%